“Reforma del art. 236 del Código Civil, en la reclamación del marido contra la paternidad del hijo concebido por su esposa durante el matrimonio - Cabrera Montoya, Ángel Fausto (2015)
The Article 236 of the Civil Code allows the husband to claim paternity of a child conceived by his wife during the marriage within sixty days from that in which delivery was aware, constituting a discriminatory rule which deprives the right of people to the defense indicated in Article 76 paragraph 7 of the Constitution of the Republic of Ecuador, that : a) no one shall be deprived of the right to defense at any stage or extent of the procedure; b ) Have the appropriate time and facilities for the preparation of his defense; c ) To be heard in a timely manner and on equal terms. If a parent decides to claim paternity of the child, by the judgment of paternity, to know that a child born in wedlock is not yours, you are being denied the right to take legal action, as the advance of science makes it viable to be checks reliably of a child born in wedlock or not his, thus if this action is limited with the passage of time that is sixty days from that on which learned of the birth, and that he could not present during that time, is a breach of law, then contrasts the merits of the substantive law by which rights and duties are developed, creating legal uncertainty for people who believe that a particular child is not his